2005
DOI: 10.1165/rcmb.2005-0100oc
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10–Secreting “Regulatory” T Cells Induced by Glucocorticoids and β2-Agonists

Abstract: Greater clinical benefit in controlling the symptoms of asthma is frequently observed through combining moderate doses of inhaled glucocorticoids together with long-acting beta(2)-agonists, as compared with increasing glucocorticoid dosage alone. To address in vitro whether glucocorticoids plus beta(2)-agonists, compared with glucocorticoids alone, have greater inhibitory activity on CD4+ T cell responses to allergen, peripheral blood CD4+ T cell responses to allergen were compared in the presence or absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 33 publications
6
47
2
Order By: Relevance
“…However, it may also be possible to achieve similar cooperative effects between glucocorticoids and other drugs for induction of IL-10-secreting Tregs. Indeed, our recent studies demonstrate a similar capacity upon combining glucocorticoids with long-acting β 2 -agonists to induce an IL-10-secreting Treg profile (37).…”
Section: Discussionmentioning
confidence: 81%
“…However, it may also be possible to achieve similar cooperative effects between glucocorticoids and other drugs for induction of IL-10-secreting Tregs. Indeed, our recent studies demonstrate a similar capacity upon combining glucocorticoids with long-acting β 2 -agonists to induce an IL-10-secreting Treg profile (37).…”
Section: Discussionmentioning
confidence: 81%
“…Other drug combinations also clearly promote IL-10 secreting Treg populations. For example, glucocorticoids in combination with long-acting b2 agonists can also induce allergen-specific regulatory T cells when used in culture of naı¨ve T cells from the peripheral blood of asthmatics (121), although this drug combination was not as effective as the original dexamethasone plus calcitriol combination. These data further suggest that vitamin D may be important in immune homeostasis in the lung.…”
Section: Pharmacological Treatments For Asthma Are Able To Modify Thementioning
confidence: 99%
“…It could be hypothesized that steroid treatment of these patients might contribute to the loss of the regulatory function of these cells. However, it has been reported that dexamethasone induces, rather than decreases, the production of IL-10 by human CD4+T cells in vitro [26,27,28]. Moreover, Matsumoto et al [29] have shown that production levels of IL-10 by circulating CD4+ CD45RO+ T cells in response to stimulation with dexamethasone did not differ between mild and severe asthmatic patients and that, although a significantly lower frequency of IL-10-producing T cells was observed in uncontrolled as compared with controlled severe asthmatics, this decrease could not be explained by the effect of high-dose inhaled corticosteroid medication.…”
Section: Discussionmentioning
confidence: 99%